5-azacitidine in aggressive myelodysplastic syndromes regulates chromatin structure at PU.1 gene and cell differentiation capacity - Curik, N; Burda, P; Vargova, K; Pospisil, V; Belickova, M; Vlckova, P; Savvulidi, F; Necas, E; Hajkova, H; Haskovec, C; Cermak, J; Krivjanska, M; et al. (Leukemia, 2012)
Epigenetic 5-azacitidine (AZA) therapy of high-risk myelodysplastic syndromes (MDS) and acute myelogenous leukemia (AML) represents a promising, albeit not fully understood, approach. Hematopoietic transcription factor PU.1 is dynamically regulated by upstream regulatory element (URE), whose deletion causes downregulation of PU.1 leading to AML in mouse. In this study a significant group of the high-risk MDS patients, as well as MDS cell lines, displayed downregulation of PU.1 expression within CD34+ cells, which was associated with DNA methylation of the URE. AZA treatment in vitro significantly demethylated URE, leading to upregulation of PU.1 followed by derepression of its transcriptional targets and onset of myeloid differentiation. Addition of colony-stimulating factors (CSFs; granulocyte-CSF, granulocyte-macrophage-CSF and macrophage-CSF) modulated AZA-mediated effects on reprogramming of histone modifications at the URE and cell differentiation outcome. Our data collectively support the importance of modifying the URE chromatin structure as a regulatory mechanism of AZA-mediated activation of PU.1 and induction of the myeloid program in MDS.
Keywords: trans-aktivátory; Antimetabolites, Antineoplastic; Female; azacytidin; Cell Line, Tumor; ženské pohlaví; Trans-Activators; Chromatin; nádorové buněčné linie; buněčná diferenciace; lidé; regulační oblasti nukleových kyselin; Azacitidine; Aged, 80 and over; protoonkogenní proteiny; metylace DNA; regulace genové exprese u leukemie; Myelodysplastic Syndromes; myelodysplastické syndromy; Male; Aged; Neoplastic Stem Cells; Regulatory Sequences, Nucleic Acid; chromatin; faktory stimulující kolonie; protinádorové antimetabolity; DNA Methylation; Proto-Oncogene Proteins; aktivace transkripce; Gene Expression Regulation, Leukemic; lidé středního věku; Cell Differentiation; senioři nad 80 let; senioři; mužské pohlaví; Colony-Stimulating Factors; Middle Aged; Transcriptional Activation; nádorové kmenové buňky; Humans